Co-treatment of Brazilein Enhances Cytotoxicity of Doxorubicin on WiDr Colorectal Cancer Cells Through Cell Cycle Arrest - Diah Tri Utami; Nadzifa Nugraheni; Riris Istighfari Jenie; Edy Meiyanto (The Indonesian Biomedical Journal, 2020)
BACKGROUND: The presence of adverse side effects limits the use of doxorubicin (Dox) despite its cost-effectiveness compared to other chemotherapeutic agents. Brazilein (Be), the major compound of Caesalpinia sappan, performs co-chemotherapeutic potency in several cancer cell lines. This study evaluates the chemosensitizing effects of Be to Dox on colon cancer cell line, WiDr.METHODS: The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay was conducted to evaluate the cytotoxic effect of Be and its combination with Dox. The synergistic effect of Be and Dox was examined by using the Combination index (CI) parameter. Cell cycle and apoptosis profiles were done using flow cytometry with propidium iodide (PI)/RNase and Annexin V staining, respectively.RESULTS: The combination of Dox and Be at half of IC50 on WiDr cells showed a synergistic effect with a combination index of 0.4. Analysis of the cell cycle revealed that the combination caused cell cycle termination at the S and G2/M phase. This finding corresponded with the data that single treatment of Dox and Be induced cell cycle arrest at the different phases, namely S and G2/M phase, respectively. However, the combination treatment for 24 hours did not induce apoptosis. This combination should be further clarified as there was a possibility that many cells may underwent permanently arrest that halts to proceed apoptosis.CONCLUSION: Our findings suggested that Be synergizes with Dox to suppress the growth of WiDr cells via cell cycle arrest, hence, Be is potential to be developed as a co-chemotherapeutic agent. Our findings suggested that Be synergizes with Dox to suppress the growth of WiDr cells via cell cycle arrest, hence, Be is potential to be developed as a co-chemotherapeutic agent.KEYWORDS: Brazilein, colon cancer WiDr, co-treatment, Doxorubicin, cell cycle arrest